Uphill filling system for a bar-like casting - Fawzi Belblidia (Journal of Materials Processing Technology, 2018)
Bar-like sand mould tilted angle reduced free surface fluctuations. The primary and secondary reflected wave heights decreased with the scaling of Re0.8 and Re0.55, respectively. These heights were reduced by 54% and 51% when θ was increased from 0° to 5°. A larger tilted angle was found to generate an air cavity in the cast, the size of which was observed to vary with Reynolds number (Re). An optimised range of tilted angle (2° to 3°) was proposed as a compromise to reduce the free surface fluctuations and maintain a perfect casting shape at the end of the filling stage.